The nature of man and his natural right in the philosophy of Spinoza - Tetiana Pavlova (Cхід)
The issue of natural law in the philosophy of Spinoza, focuses its relation to human nature in the context of social relations and relations of law. Shown realistic attitude Spinoza to human emotions and their impact on social relations. The different aspects of legal identification laws and the laws of nature, especially considered the law, which depends on natural necessity and the law, which depends on human will. The features of the contract theory of the state and pre-state condition.